A COMPARATIVE-STUDY OF 4 DIFFERENT STAINING METHODS FOR ESTIMATION OF LIVE YEAST FORM CELLS OF PARACOCCIDIOIDES-BRASILIENSIS - Sano, A.; Kurita, N.; Coelho, Kunie Iabuki Rabello [UNESP]; Coelho, R.; Takeo, K.; Nishimura, K.; Miyaji, M. (Kluwer Academic Publ, 1993)
A comparative study of four different staining methods for estimation of live yeast form cells of Paracoccidioides brasiliensis was carried out. The staining methods used were fluorescent staining, vital dye exclusion tests with erythrosin B and by Janus green and lactophenol cotton blue staining. Colony forming units (cfu) of the yeast form of eight P. brasiliensis isolates on brain heart infusion agar (BHIA) supplemented with 4% horse serum plus 5% P. brasiliensis cell extract (BHIA + HS + EXT) were examined for reliability of staining in determining the number of live fungal units in eight different isolates. Cfu on BHIA + HS + EXT plates showed an excellent plating efficiency over 96% in all isolates tested. The percentage of the live cells indicated by fluorescent staining (FL) or vital dye exclusion test with erythrosin B (EB) or Janus green (JG-1) was lower than that of cfu. By contrast, the percentage due to modified dye exclusion test with Janus green (JG-2) and that due to lactophenol cotton blue staining (LPCB) showed a close correration to that of cfu. Our results indicate that the modified dye exclusion test with Janus green and lactophenol cotton blue staining are useful for estimating cell viability of yeast form cells of P. brasiliensis.
Keywords: CELL VIABILITY; PARACOCCIDIOIDES BRASILIENSIS; STAINING METHOD